Islamic Education and Religious Environment Shape Migrant Worker Ethics: Pendidikan Agama Islam dan Lingkungan Religius Membentuk Etika Pekerja Migran - Alfarizi, Salman; Ali, Moh; Hidayat, Ade (Halaqa: Islamic Education Journal, 2026)
General Background: International migration of Indonesian Migrant Workers (PMI) to Saudi Arabia has evolved into a complex socio-religious phenomenon requiring the maintenance of ethical behavior within a global diaspora context. Specific Background: Within the Wooden Coffee network, Islamic Religious Education (IRE) and a theocratic religious environment are central factors shaping workers’ moral conduct. Knowledge Gap: Previous studies largely focus on migrant contexts in secular societies, leaving limited empirical evidence on how structured religious education functions within a formally Islamic state environment. Aims: This study aims to empirically analyze the relationship between IRE, religious environment, and the ethical behavior of PMI. Results: Using a causal-associative quantitative approach with 100 respondents and multiple linear regression analysis, findings show that both IRE and the religious environment significantly contribute to ethical behavior (Beta = 0.451; p < 0.05), with IRE emerging as the dominant factor through structured internal reinforcement compared to external social influences. Novelty: The study integrates diaspora Islamic education with a theocratic context, highlighting the interaction between internal cognitive reinforcement and external social conditioning within a behaviorism framework. Implications: The findings underline the importance of structured religious curricula and supportive workplace environments in fostering professional ethics among migrant workers, contributing to SDG 4 on inclusive and quality education for marginalized diaspora communities. Highlights• Internalized religious learning provides stronger ethical control than workplace social pressure• Theocratic environment supports but does not surpass structured educational reinforcement• Combined cognitive and social conditioning explains professional conduct patterns KeywordsIslamic Education; Religious Environment; Migrant Workers; Ethical Behavior; Diaspora